2011
DOI: 10.1007/s10943-011-9540-2
|View full text |Cite
|
Sign up to set email alerts
|

Linking Religion and Spirituality with Psychological Well-being: Examining Self-actualisation, Meaning in Life, and Personal Growth Initiative

Abstract: Research largely shows that religion and spirituality have a positive correlation to psychological well-being. However, there has been a great deal of confusion and debate over their operational definitions. This study attempted to delineate the two constructs and categorise participants into different groups based on measured levels of religious involvement and spirituality. The groups were then scored against specific measures of well-being. A total of 205 participants from a wide range of religious affiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 43 publications
9
95
2
12
Order By: Relevance
“…This further implies that despite the religious divide between the Muslim and Christian families, there are shared commonalities between them, and that the so called ‗division/schism' between the two sects is man-made or at least blurring: may be due to acculturation. The fundamental role of prayers in families' meal behaviour emphasised in this study reflects those of Burton and Clements (2013); Dobratz (2013); and Ivtzan (2013), that prayer at family mealtimes brings unity and that difference in the type of food eaten by families are largely influenced by spiritual beliefs. The aspect of family religious values were also emphasised by Cohen and Hill (2007); Reeve (2004); and Cleveland et al (2016) as instruments to promote national unity and maintain national identity.…”
Section: Discussion:-supporting
confidence: 65%
See 1 more Smart Citation
“…This further implies that despite the religious divide between the Muslim and Christian families, there are shared commonalities between them, and that the so called ‗division/schism' between the two sects is man-made or at least blurring: may be due to acculturation. The fundamental role of prayers in families' meal behaviour emphasised in this study reflects those of Burton and Clements (2013); Dobratz (2013); and Ivtzan (2013), that prayer at family mealtimes brings unity and that difference in the type of food eaten by families are largely influenced by spiritual beliefs. The aspect of family religious values were also emphasised by Cohen and Hill (2007); Reeve (2004); and Cleveland et al (2016) as instruments to promote national unity and maintain national identity.…”
Section: Discussion:-supporting
confidence: 65%
“…Nevertheless, many researchers described religion as the external or outward expression of the inward spiritual system (Dobratz, 2013;Ivtzan, 2013;and Pompper, 2014). Johnson (2014) provided a contrary perspective to the argument by suggesting that religion is concerned with addressing the crises of human existence.…”
Section: Int J Adv Res 5(1) 2675-2693mentioning
confidence: 99%
“…In addition to the aforementioned relationships, it was demonstrated that PGI was positively associated with greater career exploration, clarity regarding the vocational identity (Bartley & Robitschek, 2000;Robitschek & Cook, 1999), and spirituality (Ivtzan et al, 2011). It has been observed that the presentation of some behaviors that may contribute to the development of the individual is associated with higher levels of PGI, such as the effective use of adaptive coping strategies (e.g., problem-focused coping, Weigold & Robitschek, 2011), choosing to engage in psychotherapeutic treatments (Klockner & Hicks, 2008;Oluyinka, 2011), as well as the commitment to the psychotherapy process performed (Robitschek & Hershberger, 2005) and the tendency to develop behaviors out of the individual's comfort zone (Lasun & Odufowokan, 2012;Ogunyemi & Mabekoje, 2007).…”
Section: Personal Growth Initiative and Relationships With External Vmentioning
confidence: 99%
“…Bireysel gelişim olgusu bireylerin yaşam çizgileri boyunca çok çeşitli zorluklar ve tecrübeler yaşadığı düşüncesine odaklanır ve sürekli bireysel gelişimin, psikolojik açıdan sağlıklı kalabilmek için gerekliliğini ortaya koymaktadır (Ivtzan, Chan, Gardner ve Prashar, 2009). Bireysel gelişim inisiyatifi yapısını ilk kez kavramsallaştıran Robitschek (1997) bu yapıyı, esas olarak "bireysel gelişim sürecine aktif ve istendik katılım" olarak tanımlamaktadır.…”
Section: Introductionunclassified